American assassin : a thriller - Flynn, Vince, 1966-2013. (New York : Atria Books, 2010)
Follow Mitch Rapp, as he takes on his first explosive counterterrorism assignment.
Keywords: Rapp, Mitch (Fictitious character) -- Fiction; Terrorism -- Prevention -- Fiction; Intelligence officers -- Fiction; Suspense fiction